PEMAHAMAN KEBERAGAMAAN DAN GERAKAN KELOMPOK FPI SURABAYA - Ma’arif, Syamsul (TEOLOGIA, 2012)
Abstract: Attitudes of FPI (Islamic Defenders Front) in Indonesia so far Â impressed frontal and against any form of indecent behavior. Their action, in fact it can be said as one of the deepest expression of a group of Muslims in articulating religious teachings are embraced, or as an attitude of